2022
DOI: 10.1099/ijsem.0.005598
|View full text |Cite
|
Sign up to set email alerts
|

Description of Halosolutus amylolyticus gen. nov., sp. nov., Halosolutus halophilus sp. nov. and Halosolutus gelatinilyticus sp. nov., and genome-based taxonomy of genera Natribaculum and Halovarius

Abstract: Three extremely halophilic archaeal strains (LT55T, SQT-29-1T and WLHS5T) were isolated from Gobi saline soil and a salt lake, China. These strains were most related to the genera Natribaculum and Halovarius (92.6–95.1 % similarities), and showed low similarities with other genera within the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In the phylogenomic tree, most representatives of the 76 genera clustered with each other forming a genus clade, except for three species, Halopiger djelfimassiliensis , Halopiger goleimassiliensis and Natrialba swarupiae , which did not cluster with the other species of their respective genera. The topology of this tree indicated that Halopiger djelfimassiliensis is related to the species of the genus Halosolutus [20]; Halopiger goleimassiliensis is a species of the genus Natrarchaeobaculum ; and Natrialba swarupiae should be assigned to the genus Natrarchaeobius . Putting aside these three problematic species, the current 76 genera with validly published names gathered into eight, tightly clustered, monophyletic groups which were supported by high bootstrap values and separated from the ‘ Halorutilaceae ’ of the ‘ Halorutilales ’ recently described by Durán-Viseras et al [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phylogenomic tree, most representatives of the 76 genera clustered with each other forming a genus clade, except for three species, Halopiger djelfimassiliensis , Halopiger goleimassiliensis and Natrialba swarupiae , which did not cluster with the other species of their respective genera. The topology of this tree indicated that Halopiger djelfimassiliensis is related to the species of the genus Halosolutus [20]; Halopiger goleimassiliensis is a species of the genus Natrarchaeobaculum ; and Natrialba swarupiae should be assigned to the genus Natrarchaeobius . Putting aside these three problematic species, the current 76 genera with validly published names gathered into eight, tightly clustered, monophyletic groups which were supported by high bootstrap values and separated from the ‘ Halorutilaceae ’ of the ‘ Halorutilales ’ recently described by Durán-Viseras et al [8].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the genera Halomicrococcus [28] and Halorussus [29] were found to be two relatives of the genus Haladaptatus and should be assigned to the family ‘ Haladaptataceae ’. The Natrialbaceae cluster contains 19 genera, Halobiforma [30], Halopiger [31], Halosolutus [20], Halostagnicola [32], Haloterrigena [33], Halovivax [34], Natrarchaeobaculum [35], Natrarchaeobius [36], Natrialba [37], Natribaculum [38], Natrinema [39], Natronobacterium [40], Natronobiforma [41], Natronococcus [40], Natronolimnohabitans [35], Natronorubrum [42], Natronolimnobius [43], Salinadaptatus [44] and Saliphagus [45]. The family Natronoarchaeaceae has been described recently within the order Halobacteriales , composed of the genera Halostella [46] , Natranaeroarchaeum [7], Natronoarchaeum [47] and Salinarchaeum …”
Section: Resultsmentioning
confidence: 99%
“…The PHA biosynthesis genes of strains ZS-10 T and GSL13 T were explored based on the genome sequences [29]. Both strains contained the gene cluster encoding for PhaB, PhaC, PhaE, PhaP and PhaR in their genomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biotechnological potential of functional genes was referenced to the approach described by Sun et al . [33]. OrthoVenn2 [34] was used to compare the orthologous gene clusters (OCs) among strains Gai3-17 T , XZYJT26 T , Halobacterium salinarum DSM 3754 T , Halobacterium jilantaiense CGMCC 1.5337 T and Halobacterium litoreum ZS-54-S2 T .…”
Section: Methodsmentioning
confidence: 99%
“…The genomes of strains Gai3-17 T and XZYJT26 T were annotated utilizing Rapid Annotation using Subsystems Technology (rast) to explore the potential physiological functions of the strains. The biotechnological potential of functional genes was referenced to the approach described by Sun et al [33]. OrthoVenn2 [34] was used to compare the orthologous gene clusters (OCs) among strains Gai3-17 T , XZYJT26 T , Halobacterium salinarum DSM 3754 T , Halobacterium jilantaiense CGMCC 1.5337 T and Halobacterium litoreum ZS-54-S2 T .…”
Section: Genome Analysismentioning
confidence: 99%